2015
DOI: 10.1093/asj/sjv017
|View full text |Cite
|
Sign up to set email alerts
|

Histologic, Molecular, and Clinical Evaluation of Explanted Breast Prostheses, Capsules, and Acellular Dermal Matrices for Bacteria

Abstract: 4 Therapeutic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 104 publications
0
21
0
Order By: Relevance
“…Curiously, a histological study 42 found that mast cells, the predominant inflammatory cell in hypertrophic scars, disappear as the capsular contracture becomes more severe. Poppler et al, 43 using specialized cultures and scanning electron microscopy in women undergoing expander/implant exchange, were unable to find a correlation between biofilm formation and capsular contracture. These investigators 43 theorize that stressful stimuli might lead independently to inflammation and a biofilm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Curiously, a histological study 42 found that mast cells, the predominant inflammatory cell in hypertrophic scars, disappear as the capsular contracture becomes more severe. Poppler et al, 43 using specialized cultures and scanning electron microscopy in women undergoing expander/implant exchange, were unable to find a correlation between biofilm formation and capsular contracture. These investigators 43 theorize that stressful stimuli might lead independently to inflammation and a biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…Poppler et al, 43 using specialized cultures and scanning electron microscopy in women undergoing expander/implant exchange, were unable to find a correlation between biofilm formation and capsular contracture. These investigators 43 theorize that stressful stimuli might lead independently to inflammation and a biofilm. Paradoxically, antimicrobial therapy may even induce biofilm formation to confer resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It must also be noticed that not all capsules are associated with biofilm. 43 The reason to perform this technique is 2-fold. Firstly, to have the implant lie on a "new" raw surface, even in cases that present with no complication (ie, size change).…”
Section: Discussionmentioning
confidence: 99%